Gender, tenure and the pursuit of work-life-family stability - Willmott, Kristen E. (Work-life balance., 2020)
"Female faculty underrepresentation in higher education is perpetuated by gender-based social and professional practices and roles. Existing research confirms gender disparities in faculty recruitment, retention, salary, tenure, and mentorship. This book explores how female, tenure-track faculty navigate the process of balancing their personal and professional lives. Utilizing a qualitative phenomenological approach, the stories of nine female, full-time tenure-track and tenured faculty as well as four administrators employed in faculty diversity, development, and work-life are explored. With a blended application of post-structuralist feminism and work-family border theoretical framework, the book illustrates gender norms, roles, and boundaries as experienced and interpreted by female faculty navigating their work, family, and community spheres of influence. This book highlights the first known study to explore a "new Ivy" institution, and there are no other known studies that incorporate both the qualitative perspectives of female faculty as well as those of the faculty diversity and development administrators who oversee and develop the very programs and policies that support those faculty. A key chapter in the book, "Baby, It's Cold Inside: Faculty Context & Campus Climate" offers unique insight into what female faculty, and those who love them, face on the path to tenure today. Five thematic findings are overviewed and explored: faculty support comes in many forms; seeking clarity in job elements and teaching, research, service (TRS) ratios; coping strategies in the wake of an overloaded TRS ratio ("Quick meals, late nights, and what gym?"); family borders in the academy, and work-life-family fit: stability, not balance. This work aims to stimulate faculty gender norm consciousness and acknowledge and relay the unique challenges in faculty's pursuit of work-life-family stability, career path navigation, and role negotiation. The author offers an insider's glimpse of modern faculty and administrator lives for the benefit of tenure-track faculty, their departments, their families, and higher education institutions at large. This work aims to better inform university and departmental policy planning and enhance institutional understanding and subsequent support in and of the faculty experience, and thus the experiences of the increasingly diverse students whom educational institutions aim to serve"--